The Strategy of Badan Informasi Geospasial For Indonesia s Geospatial Infrastructure Information Development - Kurniawan, Risky (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2024)
Indonesia's national development needs geospatial information (GI) as a guidance. The existing GI can be implemented well if Indonesia has better geospatial information infrastructure (GII). The GII dimensions are policies, institutions, technology, standards and human resources (HR). However, the GI produced across sectors still experiences overlap.  This study uses the literature study method and using the comparative analysis method to comparing policies in Indonesia with several countries. This study provides policy options for the Badan Informasi Geospasial to prepare a comprehensive study of the condition of GII in Indonesia relating to state institutions, inventory the existing conditions of the five dimensions of GII in all agencies, carry out an inventory of policies and standards that will cover, and create a road map for HR training and technology for organizing GI, and carry out concrete cooperation and training with government agencies that still inadequate in implementing GI and developing GII.